OCEAN FOR LIFE AND THE MISSION TO INCREASE INCOME FOR TARGET COMMUNITIES AROUND THE GULF OF THAILAND: ANALYSIS OF PERFORMANCE AND RECOMMENDATIONS - Teera Sindecharak; Ekasit Nunbhakdi; Kanjana Boonyoung; Saowathan Phoglad; Akkaranai Kwanyou; Saranya Tarat; Wanwiwat Ruttanalum (PEOPLE: International Journal of Social Sciences, 2025)
The "Ocean for Life" project by PTT Exploration and Production Public Company Limited (PTTEP) aims to conserve and restore marine ecosystems while supporting economic growth and improving the quality of life in coastal communities. To achieve this, PTTEP has implemented a marine aquaculture learning center and a seafood product development project in 17 provinces around the Gulf of Thailand. The goal is to boost the income of participating communities. To ensure the project’s effectiveness and standards, PTTEP commissioned Thammasat University’s Research and Consulting Center to study and evaluate the income of the target communities. The study found that the ongoing marine learning center project significantly increased marine life, leading to higher fish catches and helping to preserve local fishing jobs and reduce migration. However, the value of the catch did not increase proportionally with the amount caught. Key factors affecting income include boat operating expenses and maintenance costs, which vary by boat size and type. Although the seafood product development project increased the quantity and variety of processed seafood, it did not significantly boost income for members compared to the learning center project. This is due to the abundance of similar products in the market, limited distribution methods, and inconsistent pricing. The research center recommended improvements in research and project development to help "Ocean for Life" achieve its future objectives.